Expression and purification of bioactive, low-endotoxin recombinant human vitronectin. (June 2014) - Halford, Michael M.; He, Yi-Chao; Stacker, Steven A.
The secreted adhesive glycoprotein vitronectin (VTN) is a multifunctional component of plasma and the extracellular matrix. A high-yielding, inexpensive, low endotoxin source of bioactive recombinant human vitronectin (rhVTN) is highly desirable for in vitro use in diverse cell culture systems ranging from basic research settings to clinical-grade production of human cells. We describe modifications to a previously reported heparin-based affinity chromatography procedure that improve yield and achieve efficient removal of endotoxin from washed and urea-solubilized human VTN inclusion bodies following standard autoinduction of expression in Escherichia coli . This simple procedure makes accessible the low-cost expression and purification of large quantities of bioactive rhVTN using basic equipment and facilitates its use in a spectrum of endotoxin-sensitive applications.